Pengungkapan Corporate Social Responsibility Sebagai Pemoderasi Pengaruh Leverage dan Kepemilikan Manajerial Pada Nilai Perusahaan - Shinta Vidarani, Ida Ayu Gde; Nyoman Budiasih, I Gusti Ayu (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p11, 2020)
ABSTRACT This study aims to determine and obtain empirical evidence about the effect of leverage and managerial ownership on firm value by disclosing corporate social responsibility as a moderating factor. This research was conducted on mining companies listed on the Indonesia Stock Exchange in 2014-2018. The research sample was selected using the nonprobability sampling method with a purposive sampling technique and obtained 13 mining companies, so the number of observations in the study was 65 observations over 5 years. Data analysis techniques used is Moderated Regression Analysis (MRA). Based on the results of the study, it shows that disclosure of corporate social responsibility as a moderating variable weakens the influence of leverage on firm value, disclosure of corporate social responsibility as a moderating variable that strengthens the effect of managerial ownership on firm value . Keywords : Csr disclosure, leverage, managerial ownership, firm value